Lingkungan Pendidikan Islam Perspektif Hadis - Dalmi Iskandar Sultani; Syamsu Nahar (Journal Analytica Islamica, 2022)
Education plays an important role today, because without education the process of modern knowledge transformation will be difficult to do. Educators must also adjust themselves by continuously learning to add and hone their abilities in order to take part in the transfer of knowledge, otherwise they will be replaced by technology. In addition, the development of learner progress is also dominated by the environment in its journey. In this paper, it will be discussed specifically about the environment of Islamic Education from the perspective of the prophet's hadith. This research was conducted using a qualitative approach with a literature review. The data collected comes from references that are accurate and relevant to the discussion being studied.